Предмет: Алгебра,
автор: olesya200254
Преобразуйте выражение в многочлен
стандартного вида
Приложения:
Ответы
Автор ответа:
0
Решение
в) 3y*(³ - 3y - 4) = 3y⁴ - 9y² - 12y
г) - 5mn*(m³ + 3m²n - n³) = - 5m⁴n - 15m³n² + 5mn⁴
в) 3y*(³ - 3y - 4) = 3y⁴ - 9y² - 12y
г) - 5mn*(m³ + 3m²n - n³) = - 5m⁴n - 15m³n² + 5mn⁴
Похожие вопросы
Предмет: Математика,
автор: margaritacertan
Предмет: Другие предметы,
автор: zanajymzakynbek
Предмет: Биология,
автор: zansaaramazanova318
Предмет: Математика,
автор: JeneParker
Предмет: Алгебра,
автор: ksenichka44